2022
DOI: 10.7759/cureus.27169
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Carpal Tunnel Release Using Ultrasound Guidance in a Community Setting: Long-Term Results

Abstract: Objectives: To report the safety and effectiveness of office-based carpal tunnel release (CTR) using ultrasound (US) guidance in a general community population. Methods: This was a prospective single-center study that evaluated patients treated with CTR using US guidance between March 2019 and August 2020 for whom one-year data were available. Procedures were performed in an office-based procedure room using local anesthesia. Main outcomes of this study included complications, Boston Carpal Tunnel Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…The 1-year results with CTR-US in this trial corroborate the long-term results reported in single-arm CTR-US studies 8–11 that reported sustained and clinically important improvements in CTS symptoms with a low rate of complications (Table 2). In this trial, more than one in four patients assigned to mOCTR withdrew before treatment because they did not desire mOCTR despite initially consenting to randomization.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The 1-year results with CTR-US in this trial corroborate the long-term results reported in single-arm CTR-US studies 8–11 that reported sustained and clinically important improvements in CTS symptoms with a low rate of complications (Table 2). In this trial, more than one in four patients assigned to mOCTR withdrew before treatment because they did not desire mOCTR despite initially consenting to randomization.…”
Section: Discussionsupporting
confidence: 86%
“…This learning curve with CTR-US is consistent with previous studies demonstrating proficiency by providers with a wide range of prior experience in ultrasound and CTR. 10,23 While the substantial difference in surgeon experience precluded statistically analyzing its impact on trial results, comparing CTR-US and mOCTR outcomes among similarly experienced surgeons would be informative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound helps the operator perform the procedure through a small incision while providing an expanded field of view, including multiplanar and dynamic views, compared to endoscopic and similar small incision techniques. Numerous studies have demonstrated the safety and effectiveness of CTR-US for the treatment of CTS [8][9][10][11][12], yet clinical outcomes with this procedure when performed in-office are not well characterized. A prospective single-center study demonstrated the feasibility of CTR-US when performed in an office-based setting [8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the safety and effectiveness of CTR-US for the treatment of CTS [8][9][10][11][12], yet clinical outcomes with this procedure when performed in-office are not well characterized. A prospective single-center study demonstrated the feasibility of CTR-US when performed in an office-based setting [8]. The improvement in CTS symptoms following office-based CTR-US was statistically significant and clinically important over one year of follow-up, and no intraoperative complications or reoperations were reported.…”
Section: Introductionmentioning
confidence: 99%